Comparison of Consumer Protection Laws Between Indonesia, the Philippines, and South Korea in Achieving Justice - Dewi, Retno Sari; Dwiatmanto, Dwiatmanto; Surjanti, Surjanti (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Consumer protection is an important aspect as a global phenomenon and is practically implemented by various countries in the world.Purpose of the Research: This research aims to describe the development of consumer protection regulations in Indonesia and to compare consumer protection between Indonesia, the Philippines and South Korea in realizing justice.Method of Research: Normative legal research by prioritizing comparative, conceptual and statutory approaches.Results of Research: The development of consumer protection regulations in Indonesia after the passing of the consumer protection law has actually facilitated the existence of consumer rights which are applied proportionally to consumer obligations. Even so, the practice of developments over time and technology also actually requires changes to consumer protection laws. In efforts to realize justice for consumers by referring to the consumer protection arrangements carried out by the Philippines and South Korea, Indonesia needs to optimize effective and substantive consumer complaint procedures as in the Philippines, including also referring to consumer protection practices carried out by South Korea by providing integrated legal assistance. for consumers in the consumer dispute process, both legal assistance in the form of consultations and legal assistance services in the form of lawyers for consumers.